2009
DOI: 10.1037/a0013066
|View full text |Cite
|
Sign up to set email alerts
|

Complexity and valence in ethnophaulisms and exclusion of ethnic out-groups: What puts the "hate" into hate speech?

Abstract: Ethnophaulisms (A. A. Roback, 1944) are the words used as ethnic slurs to refer to out-groups in hate speech. The results of previous archival research have suggested that it is the complexity, more so than the valence, of ethnophaulisms that predicts the exclusion of ethnic immigrant out-groups from the receiving society. This article reports the results of 3 experimental examinations of the relative contributions of complexity and valence in ethnophaulisms to the exclusion of an ethnic out-group. Experiment … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
29
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(30 citation statements)
references
References 76 publications
(139 reference statements)
1
29
0
Order By: Relevance
“…Behaviorally, hatred may lead to the desire to eradicate the hated out-group (White, 1996). Extensive research has demonstrated that in some situations, there is a connection between hate and its various active manifestations; that is, out-group exclusion (Leader & Mullen, 2009), terrorism (Sternberg, 2003), motivation to fight and kill in battle (Ballard & McDowell, 1991), and hate crimes (Berkowitz, 2005).…”
Section: The Psychology Of Group-based Hatredmentioning
confidence: 99%
“…Behaviorally, hatred may lead to the desire to eradicate the hated out-group (White, 1996). Extensive research has demonstrated that in some situations, there is a connection between hate and its various active manifestations; that is, out-group exclusion (Leader & Mullen, 2009), terrorism (Sternberg, 2003), motivation to fight and kill in battle (Ballard & McDowell, 1991), and hate crimes (Berkowitz, 2005).…”
Section: The Psychology Of Group-based Hatredmentioning
confidence: 99%
“…Furthermore, interview (e.g., Phoenix, Frosh, & Pattman, 2003;Renold, 2002;Stoudt, 2006), survey (Franklin, 2000), and experimental studies (Carnaghi et al, 2011) suggest that homophobic language goes hand in hand with the endorsement of masculine norms highlighting the deviant nature as well as a call for "punishment" of those individuals that are perceived to deviate from these norms (Pascoe, 2005;Plummer, 2001;Slaatten, Anderssen, & Hetland, 2014). In contrast to homophobic epithets (which carry an insulting and distancing motivation, Carnaghi & Maas, 2006, 2008; see also Allport, 1954;Mullen & Rice, 2003;Leader, Mullen, & Rice, 2009), category labels such as "gay" or "homosexual" are terms used to label a social group characterized by sexual orientation, carrying nowadays less evaluative weight than in the past. Hence, while category labels (for at least most people) have a primarily descriptive/denotative function (i.e., indicating men who love/have sex with other men), homophobic epithets have a defensive or value-expressive function (Herek, 1990;Jewell & Morrison, 2010).…”
mentioning
confidence: 99%
“…We also tested the impact of homophobic epithets on physical distance. Maintaining social-psychological distance from derogated individuals has emerged in studies about derogatory ethnic labels (Leader et al, 2009) but has not been tested with regard to homophobic epithets and actual behavior. Previous research has shown that people tend to maintain physical distance toward individuals labeled as deviant, perceived as dissimilar and negatively stereotyped (Heinemann, Pellander, Vogelbusch, & Wojtek, 1981;Macrae, Bodenhausen, Milne, & Jetten, 1994;Skitka, Bauman, & Sargis, 2005;Snyder & Endelman, 1979).…”
mentioning
confidence: 99%
“…Third, our data inform studies on derogatory group labels (Carnaghi & Maass, ; Carnaghi et al ., ; Greenberg & Pyszczynski, ; Leader et al ., ). Previous research on homophobic epithets was limited to attitudes or behavioural intentions.…”
Section: Discussionmentioning
confidence: 97%
“…We only used labels referring to gay men because Italian has a rich repertoire of derogatory labels for male, but not for female homosexuals. Moreover, we examined commonly used derogatory language referring to a real social group rather than fictitious labels targeting artificial groups (Leader et al, 2009). Finally, we investigated the effect of homophobic epithets on a behavioural measure of intergroup bias, namely resource allocation (Bourhis, Turner, & Gagnon, 1997;Gaertner & Insko, 2000;Mummendey et al, 1992).…”
Section: Homophobic Epithetsmentioning
confidence: 99%